Two meta-heuristic algorithms for scheduling on unrelated machines with the late work criterion - Wang, Wen; Chen, Xin; Musial, Jedrzej; Blazewicz, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
A scheduling problem in considered on unrelated machines with the goal of total late work minimization, in which the late work of a job means the late units executed after its due date. Due to the NP-hardness of the problem, we propose two meta-heuristic algorithms to solve it, namely, a tabu search (TS) and a genetic algorithm (GA), both of which are equipped with the techniques of initialization, iteration, as well as termination. The performances of the designed algorithms are verified through computational experiments, where we show that the GA can produce better solutions but with a higher time consumption. Moreover, we also analyze the influence of problem parameters on the performances of these metaheuristics.
Keywords: late work minimization; unrelated machines; tabu search; genetic algorithms